Pelatihan Pengembangan Keunggulan Bersaing UMKM Kota Batam dengan e-Commerce - Azwanti, Nurul; Putria, Narti Eka; Hakim, Arif Rahman (LPPM Universitas Putera Batam, 2024)
The implementation of community service activities will take the form of Empowerment of E-Commerce-Based Marketing located at Rindang Garden Block B2 No. 04, Buliang Village, Batu Aji District, Batam. Based on the field interview results, the Small and Medium-sized Enterprises (UMKM) Rafflesia face challenges in marketing their products. In general, UMKM businesses have limitations in mastering information technology facilities and marketing media that are not well-known to the public. Conventional business owners feel that accounting recording is a cumbersome task. The training method used is to provide training through an online website. The methods used in the development of UMKM Rafflesia include survey methods, lecture methods, discussion methods, and training methods. The sustainability of the results of this coaching activity is expected to enable UMKM Rafflesia to manage online marketing effectively.